Use of reservoir clay sediments as raw materials for geopolymer binders. (1st May 2013) - Ferone, C; Colangelo, F; Cioffi, R; Montagnaro, F; Santoro, L
<x xml:space="preserve">Abstract</x> Abstract Among low cost or readily available raw materials, reservoir clay sediments are of interest as potential precursors in geopolymer binder manufacture. These materials come from dredging of reservoirs because periodical sediment removal is necessary in order to keep a satisfactory level of functionality. In this paper, two sediments, coming from reservoirs located in Southern Italy, have undergone preliminary characterisation by X-ray diffraction, differential thermogravimetry and Fourier transformed infrared (FTIR) spectroscopy. Then, the sediments were submitted to 1 and 2 h calcination treatments at 650 and 750°C. The effects of calcination were evaluated by means of 27Al magic angle spinning nuclear magnetic resonance and FTIR. The calcined samples were mixed with 5M NaOH solution, and the obtained mixtures were studied for reactivity by means of differential scanning calorimetry. Finally, cylindrical samples were prepared with the same mixtures and cured for 3 days at 60°C plus 4 and 25 days at room temperature. The obtained samples were subjected to unconfined compressive strength determinations in order to verify the actual occurrence of geopolymerisation. The results show that the calcined clay sediments can be suitable precursors in polycondensation reactions.